Wharton Jelly Derived Mesenchymal Stem Cell's Exosomes Demonstrate Significant Antileishmanial and Wound Healing Effects in Combination with Aloe-Emodin: An in Vitro Study - Koken, Gulnaz Yildirim; Abamor, Emrah Sefik; Allahverdiyev, Adil; Karaoz, Erdal (ELSEVIER SCIENCE INC, 2022)
The aim of the present study was to explore the antileishmanial performance and wound healing effect of exosomes isolated from Wharton Jelly derived mesenchymal stem cells (WJ-MSCs) in combination with aloe-emodin. MSCs obtained from Wharton Jelly were characterized by flow cytometry. Exosomes were iso-lated from cultivated stem cells by ultacentrifugation method. Scanning Electron Microscopy (SEM), Dynamic Light Scattering (DLS), Nanoparticle Tracking Analysis (NTA) and flow cytometry were used for characteriza-tion of obtained exosomes. The cytotoxicities of characterized exosomes and aloe-emodin at different con-centrations were investigated on L929 and J774 cell lines. Non-toxic concentrations of each agent were combined and their inhibitory efficacies on L.major promastigotes and amastigotes were investigated by dif-ferent techniques such as MTT, parasite count and measurements of infection index. Finally, wound healing activities of combinations were examined on in vitro artifical wound model and compared with the use of exosomes alone. According to outcome of flow cytometic analysis, vesicles isolated from WJ-MSCs highly expressed the markers such as CD63 special for exosome profile. SEM and NTA results demonstrated that derived exosomes possessed dimensions between 150 to 200 nanometers and elicited the cup-shape specific to exosomes. Combinations including non-toxic dosages of exosomes and aloe-emodin demonstrated supe-rior antileishmanial effectivenesses both on promastigotes and amastigotes in contrast to use of exosome alone since they lead to inhibition of promastigotes and amastigotes for 4 and 10-folds in comparison to con-trol, respectively. Additionally, combinations elicited more rapidly and effective in vitro wound-healing per-formance in contrast to use of exosome alone. At the end of 24 h incubation application of combinations gave rise to wound closure at a rate of 72 %, while in the control group 52 % of wound area has not been healed, yet. These results reflect that mentioned combination has great potential to be used in treatment of cutaneus leishmaniasis (CL) since they have magnificient capacity to inhibit Leishmania parasites while enhancing wound healing. (c) 2022 Published by Elsevier Inc. on behalf of American Pharmacists Association.
Keywords: Cutaneous leishmaniasis; Aloe-emodin; Exosome; Mesenchymal stem cell; Wharton jelly; Antileishmanial activity; STROMAL CELLS; MICROVESICLES; Pharmacology & Pharmacy; Chemistry